The great philosophers : an introduction to Western philosophy - Magee, Bryan (Oxford University Press, 1988)
This work is based on a BBC television series also entitled "The Great Philosophers" and aims to provide an accessible introduction to the concepts of Western philosophy and to some of its greatest thinkers from Plato to the present day. The conversational format is intended to keep the discussion lively and clear, even when it concerns difficult ideas. Starting with the death of Socrates in 399 BC and the subsequent writings of Plato, it continues with Aristotle and the medieval philosophers, the writings of (among others) Descartes, Locke and Kant, and then on to the 20th century and the ideas of recent figures, such as Heidegger, Bertrand Russell and Wittgenstein.